Predictors for New Native-Vessel Occlusion in Patients with Prior Coronary Bypass Surgery: A Single-Center Retrospective Research - Ze Zheng; Zi chao Cheng; Shao ping Wang; Shi ying Li; Jian Wang; Hong yu Peng; Zheng Wu; Wen zheng Li; Yun Lv; Jia yu Tian; Shu juan Cheng; Jing hua Liu (Cardiology Research and Practice)
Objectives. Chronic total occlusion (CTO) is prevalent in patients with prior coronary artery bypass grafting (CABG). However, data available concerning the prevalence of new-onset CTO of native vessels in patients with prior CABG is limited. Therefore, the objective of the study is to determine predictors for new native-vessel occlusion in patients with prior coronary bypass surgery. Methods. 354 patients with prior CABG receiving follow-up angiography are selected and analyzed in the present study, with clinical and angiographic variables being analyzed by logistic regression to determine the predictors of new native-vessel occlusion. Results. The overall new occlusion rate was 35.59%, with multiple CTOs (42.06%) being the most prevalent (LAD 24.60% and RCA 18.25%, respectively). Additionally, current smoking (OR: 2.67; 95% CI: 2.60 to 2.74; p=0.01), reduced ejection fraction (OR: 1.76; 95% CI: 1.04 to 2.97; p=0.04), severe stenosis (OR: 3.65; 95% CI: 2.55 to 5.24; p=0.01), and diabetes mellitus (OR: 1.86; 95% CI: 1.34 to 2.97; p=0.04) serve as the independent predictors for new native-vessel occlusion. Conclusion. As to high incidence of postoperative CTO, appropriate revascularization strategies and postoperative management should be taken into careful consideration.